Estrutura hiperbólica no complemento do nó figura 8. - Oliveira, José Danuso Rocha de (2017)
In this work, we study the hyperbolic space and will classify its isometries by using Poincaré’s disc and half-space models. We introduce the concepts of convex polyhedra on euclidian, spheric and hyperbolic spaces, as well as in (X, G)-manifolds, in particular when X is the euclidian, spheric or hyperbolic space, and G is its respectiv group of isometries. We formalize the concept of gluing convex surfaces and polyhedra. We also give examples of gluing convex polyhedra with euclidian and hyperbolic sctructure for the complement of the 8-figure knot on the 3-sphere.